IDENTIFICATION OF DISEASE SYMPTOMS OF ARTISANAL GOLD MINERS IN TERMS OF LENGTH OF TIME WORKED (0-5 YEARS) IN THE WORKING AREA OF UPTD PUSKESMAS UJUNG PADANG RASIAN - Lensoni, Lensoni; Idroes, Ghazi Mauer; Mustafa, Mustafa (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2024)
According to WHO, mercury is a naturally occurring metallic element and is divided into three groups: liquid and gaseous mercury, inorganic mercury, and organic mercury. Mercury is the only metal that is liquid under standard conditions and vaporizes on contact with air. This study aims to identify symptoms of illness due to mercury exposure in gold mine workers at the UPTD Puskesmas Ujung Padang Rasian, South Aceh District. The study involving 24 respondents was conducted in June 2023 using a questionnaire. The results showed that the most frequent acute clinical symptoms were headache (14 respondents), cough (11 respondents), pain during urination and nausea (10 respondents each), pelvic pain (9 respondents), vomiting and bloody urine (7 respondents), cloudy urine (5 respondents), abdominal pain and numbness in the mouth (3 respondents), loose teeth and swollen gums (2 respondents), and diarrhea and dark gums (1 respondent each). Symptoms of chronic toxicity included headache (6 respondents), muscle cramps (9 respondents), irritability (2 respondents), erythema, weight loss, anorexia, anxiety, depression, insomnia and memory loss (1 respondent each). In conclusion, the majority of respondents experienced symptoms due to mercury exposure such as headache (20 respondents), pelvic pain and painful urination (14 respondents), cough (13 respondents), and nausea (12 respondents).